Cyber Security Governance: Peran Organisasi Internasional dalam Pembentukan Norma Keamanan Siber Global - Hakeem, Mirza Athaya Ghaisan; Febriza, Muhammad Dyo; Putra, Alfarel Endito (Media Hukum Indonesia (MHI), 2025)
The development of information and communication technology has significantly transformed global interactions but also generated complex and cross-border cyber threats, including ransomware, data theft, and critical infrastructure sabotage. The borderless nature of cyberspace makes it impossible for a single country to handle these threats independently, highlighting the need for internationally agreed norms and cybersecurity governance. Based on this context, this study aims to analyze the role of international organizations, such as the UN, ITU, NATO, OECD, and ASEAN, in establishing global cybersecurity norms and to explore the prospects for strengthening cybersecurity governance through international and regional cooperation. This research employs a normative juridical method with a literature review approach, analyzing international legal instruments, official documents of international organizations, and relevant academic literature on cybersecurity governance.